Chemical stability of YBiO3 buffer layers for implementation in YBa2Cu3O7-δ coated conductors. (November 2015) - Pollefeyt, Glenn; Meledin, Alexander; Pop, Cornelia; Ricart, Susagna; Hühne, Ruben; Van Tendeloo, Gustaaf; Van Driessche, Isabel
Graphical abstract: Abstract: In this work, the chemical and microstructural stability of YBiO3 buffer layers during the growth of YBa2 Cu3 O7-δ (YBCO) was studied. The superconducting YBCO films were deposited via both Pulsed Laser Deposition as well as Chemical Solution Deposition. Although excellent superconducting properties are obtained in both cases, self-field critical current densities of 3.6 and 1.2 MA/cm 2 respectively, chemical instability of the YBiO3 buffer layer is observed. An elaborate transmission electron microscopy study showed that in the case of vacuum deposited YBCO, the YBiO3 becomes unstable and Bi2 O3 sublimates out of the architecture. Due to this structural instability, an intermediate Y2 O3 layer is obtained which maintains it microstructural orientation relation with the substrate and acts as growth template for YBCO. For chemical solution deposited YBCO, reaction of YBCO with the YBiO3 buffer layer is observed, leading to large grains of YBa2 BiO6 which are pushed towards the surface of the films and strongly reduce the superconducting properties. Upon using high growth temperatures for the superconducting layer, these secondary phases decompose, which subsequently leads to Bi2 O3 sublimation and a textured YBCO film which directly nucleated onto the LaAlO3 single crystal substrate. Hence, this electron microscopy study indicates that bismuth-based buffer layers systems are not suitable for implementation in coated conductors.